Fusion via transpsoas lateral approach: considerations and initial results - Oliveira,Daniel de Abreu (2014)
OBJECTIVE: To present some technical considerations about interbody fusion by direct lateral retroperitoneal transpsoas approach and its initial results. METHODS: Non-randomized prospective study of 14 patients undergoing interbody fusion via lateral approach, with evaluation of initial results and complications. RESULTS: We collected and analyzed data from 14 patients with a total of 27 levels operated. The average operative time was 146 minutes and blood loss was on average less than 50 ml. Ten patients required supplemental percutaneous fixation with pedicle screws. VAS scores for the lumbar region and lower limbs and ODI had significant improvement in the postoperative period. There was an associated case of postoperative infection and thromboembolism that required reoperations. CONCLUSION: This technique has revolutionized the care of patients requiring fusion of T6-7 to L4-5. Following the five basic steps and using intraoperative monitoring, this technique is safe and reproducible with encouraging clinical results and low rate of serious complications.